Surviving in the hospitality industry: enhancing business performance of SP Inn Hotel / Mohd Johar Jahaya and Faizal Ahmad - Jahaya, Mohd Johar; Ahmad, Faizal (2017)
The main purpose of this study is to study and analyse the business performance of SP Inn Hotel and evaluate whether it can survive in the hospitality industry. The study also formulate optimum strategies to enhance its business performance so as to sustain in the hospitality industry. Comprehensive analysis of its financial position, the internal as well as the external factors of SP Inn Hotel have been conducted to identify overall performance encompassing financial ratio analysis, breakeven point analysis and business environment analysis. Breakeven point analysis is used to identify room sales and average room rate and financial ratios are used to evaluate the financial strength. Porter suggests that awareness of the five forces can help the business to understand the structure of its industry and position itself to be more profitable and less vulnerable to attack. In this study, we used Porter’s Five Forces for the assessment of industry analysis and SWOT analysis to assess overall external forces and internal factors. The findings indicated that SP Inn Hotel operating in highly competitive industry, financial ratios were far behind its competitors and room occupied was below BEP. TOWS and Ansoff Matrix were used as a tool to assist in strategic planning in various aspects of enterprise and helped to generate a number of possible alternative strategies. Based on the analysis, we proposed few strategies to assist SP Inn Hotel to enhance its business performance. It is hoped that the findings of this study can be utilized by SP Inn Hotel to evaluate its business performance and enhance it to survive in the hospitality industry.